(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the year 2007, the Government of Karnataka executed the English as a second language from the first standard in Non-English Medium schools. The Government has already approved that it had acknowledged the order after the serious examinations connecting to the implementation of the rule on the community appeal, and it has quoted the results of studies in the field of English language teaching. But some of the scholars suspected the Government’s move and objected that it was an act to protected vote bank and it did it to satisfy investors. The entire state observed tempestuous discussions around the rule.